Adjuvant Therapy of High-Risk (Stages IIC–IV) Malignant Melanoma in the Post Interferon-Alpha Era: A Systematic Review and Meta-Analysis - Christofyllakis, Konstantinos; Pföhler, Claudia; Bewarder, Moritz; Müller, Cornelia S. L.; Thurner, Lorenz; Rixecker, Torben; Vogt, Thomas; Stilgenbauer, Stephan; Yordanova, Krista; Kaddu-Mulindwa, Dominic (Frontiers in Oncology, 2021)
Introduction: Multiple agents are approved in the adjuvant setting of completely resected high-risk (stage IIC-IV) malignant melanoma. Subgroups may benefit differently depending on the agent used. We performed a systematic review and meta-analysis to evaluate the efficiency and tolerability of available options in the post interferon era across following subgroups: patient age, stage, ulceration status, lymph node involvement, BRAF status. Methods: The PubMed and Cochrane Library databases were searched without restriction in year of publication in June and September 2020. Data were extracted according to the PRISMA Guidelines from two authors independently and were pooled according to the random-effects model. The predefined primary outcome was recurrence-free survival (RFS). Post-data extraction it was noted that one trial (BRIM8) reported disease-free survival which was defined in the exact same way as RFS. Results: Five prospective randomized placebo-controlled trials were included in the meta-analysis. The drug regimens included ipilimumab, pembrolizumab, nivolumab, nivolumab/ipilimumab, vemurafenib, and dabrafenib/trametinib. Adjuvant treatment was associated with a higher RFS than placebo (HR 0.57; 95% CI= 0.45-0.71). Nivolumab/ipilimumab in stage IV malignant melanoma was associated with the highest RFS benefit (HR 0.23; 97.5% CI= 0.12-0.45), followed by dabrafenib/trametinib in stage III BRAF-mutant melanoma (HR 0.49; 95% CI= 0.40-0.59). The presence of a BRAF mutation was associated with higher RFS rates (HR 0.30; 95% CI= 0.11-0.78) compared to the wildtype group (HR 0.60; 95% CI= 0.44-0.81). Patient age did not influence outcomes (≥65: HR 0.50; 95% CI= 0.36-0.70, <65: HR 0.58; 95% CI= 0.46-0.75). Immune checkpoint inhibitor monotherapy was associated with lower RFS in non-ulcerated melanoma. Patients with stage IIIA benefited equally from adjuvant treatment as those with stage IIIB/C. Nivolumab/ipilimumab and ipilimumab monotherapy were associated with higher toxicity. Conclusion: Adjuvant therapy should not be withheld on account of advanced age or stage IIIA alone. The presence of a BRAF mutation is prognostically favorable. BRAF/MEK inhibitors should be preferred in the adjuvant treatment of BRAF-mutant non-ulcerated melanoma.